2013
DOI: 10.1134/s1062359013030102
|View full text |Cite
|
Sign up to set email alerts
|

Are the contours of the frontal section of shell valves in Bivalvia specific?

Abstract: The diagnostic importance of the character of curvature of the frontal section of shell valves in Bivalvia on the basis of determining the constant angle of the logarithmic spiral is discussed. The contours of the frontal section of shell valves in several species of mollusks of the families Margaritiferidae and Sphaeri idae have been analyzed. It is shown that in different species of the family Sphaeriidae, the values of constant angles coincide. While performing graphic constructions, it was established that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The discussion about the number of species in the freshwater pearl mussel M. margaritifera (Sergeeva et al, 2008;Bogatov, 2009Bogatov, , 2013Bolotov et al, 2013;Voroshilova, 2013) appeared within the framework of such terms as morphological species, which, accord ing to Mair (1971, p. 38) does not have any biological or, thus, scientific sense. Two species of this genus (M. elongata and M. borealis), which were singled out based on the morphological differences and contours of the frontal valves section (Bogatov et al, 2003), are not separate, because these differences are associated with interpopulational variations (Sergeeva et al, 2008;Bolotov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discussion about the number of species in the freshwater pearl mussel M. margaritifera (Sergeeva et al, 2008;Bogatov, 2009Bogatov, , 2013Bolotov et al, 2013;Voroshilova, 2013) appeared within the framework of such terms as morphological species, which, accord ing to Mair (1971, p. 38) does not have any biological or, thus, scientific sense. Two species of this genus (M. elongata and M. borealis), which were singled out based on the morphological differences and contours of the frontal valves section (Bogatov et al, 2003), are not separate, because these differences are associated with interpopulational variations (Sergeeva et al, 2008;Bolotov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The contours of the frontal section of valves were not tested as a diagnostic feature, because it is proved that the comparative method is not appropriate for this purpose, especially for large sized shells (Sergeeva et al, 2008;Bolotov et al, 2013;Voroshilova, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…His studies, based on protein electrophoresis, showed that several Unionidae species determined by the comparatorial method had no molecular biological differences [Kodolova, Logvinenko, 1973, 1974. Voroshilova [2013] demonstrated that the contour of the frontal shell section does not always correspond to the logarithmic spiral and the values of the axis of the polar angle can overlap even in traditionally accepted species of the genera Sphaerium Scopoli, 1777, and Margaritifera Schumacher, 1816. It has been shown that there is no hiatus in the relative morphometric proportions between the species of the genus Mar- [Sergeeva et al, 2008], and there occurs transition of the contour of the frontal shell section between them [Bolotov et al, 2013].…”
Section: Introductionmentioning
confidence: 99%